Colisão entre a dignidade da pessoa humana investigada e a liberdade de informação jornalística: proposta de solução lastreada no critério da ponderação de valores, através da aplicação do princípio da proporcionalidade - Souza, Sérgio Ricardo de (2004)
With the arrival of the Brazil Federative Republic Constitution of 1988, that represents the knowing synthesis and the dominant values in several brazilian society segments that were representative to the representatives, the patriotic juridical ordering was riched by the inclusion of several principles that in some situations enter in collision route, when they are practiced in the same time, as can be verified in connection with the developed theme that focuses the practice in which is becoming more and more usual nowadays by both members of the Police force and the press. It refers to exposing the name and/or the image of Citizens, still during the process of accomplishment of the formalities in law, or even before the establishment of a police inquiry, under the allegation that this practice is dully supported and granted by the freedom rights of the Press and the journalistic information. Nevertheless, this exposure can be offensive to the accused person' dignity, because in same cases, there is no proof of relevant public interest in the disclosing and exposition of those information that deals with the defendant personality. This matter carries a real collision with what is worth (people's values, protected by constitutional principles inserted on the 1988 Brazilian Constitution (The Citizen Constitution), that founds the solutions to give guarantee to people rights with the utilization of values ponderation, through Weighing of Values, based on the Principle of Proportionality, developed and supported by the German Constitutional Court precedents and theorized in that country, mainly by Karl Larenz and Roberty Alexy and in the United States of America by Ronald Dworkin, therefore allowing to the conclusion that, when there is evidence of public interest in the propagation, then Liberty for Journalistic Information must prevail. On the other hand, when this interest is not properly shown, protection to Human Being Under Investigation's Dignity will prevail, and the treatment which ought to be given is to allow the divulgation of the fact, without any reference to any characteristics or personal data of the indict, or suspected, as provided and determined by Law number 8.069, from 1990.